Microbiologic Examination of Bandage Contact Lenses Used after Corneal Collagen Cross-linking Treatment. (3rd March 2016) - Yuksel, Erdem; Yalcin, Nuriye Gokçen; Kilic, Gaye; Cubuk, Mehmet Ozgur; Ozmen, Mehmet Cuneyt; Altay, Aylin; Çağlar, Kayhan; Bilgihan, Kamil
Abstract: Purpose : To investigate the agents of bacterial contamination of contact lenses after corneal collagen cross-linking (CCL), and to present the possible changes of ocular flora after riboflavin/ultraviolet A. Methods : Seventy-two contact lenses of patients who underwent CCL and 41 contact lenses of patients who underwent photorefractive keratectomy (PRK) as control group were enrolled to the study. After 48 h of incubation, broth culture media was transferred to plates. Samples were accepted as positive if one or more colony-forming units were shown. Results : There were positive cultures in 12 (16.7%) contact lenses in the CCL group and 5 (12.2%) had positive cultures in PRK group. Coagulase-negative staphlycocci (CNS) were the most frequent microorganism. Alpha hemolytic streptococci and Diphteroid spp. were the other isolated microorganisms. Conclusions : Bacterial colonization can occur during and early after the CCL procedure in epithelial healing. To prevent corneal infections after the treatment, prophylactic antibiotics should be prescribed.